Response of Three Indigenous Pulse Crops to Different Moisture Conditions - Elgasim, Rahamtalla Mahgoub Abu; El Nadi, Abdel Mohsin Hassan (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted in the Demonstration Farm of the Faculty of Agriculture, University of Khartoum for two seasons (January to May 2005 and December 2005 to May 2006). The objective of the experiment was to study the effect of 7 and 14 days irrigation intervals on growth and yield of three local pulse crops; namely, Vigna unguiculata ‘Lubia Hilu’, V. sinensis ‘Lubia Kordofani’ and Lablab purpureus ‘Lubia Afin’. The results showed that irrigation every 14 days reduced dry matter production and seed yield, but increased the percentage of crude protein in the seeds of the three crops as a result of increase in the ratio proteins: carbohydrates